Surface integrity analysis before and after machining of additively manufactured (3D printed) 316L stainless steel using Selective Laser Melting (SLM) and Electron Beam Melting (EBM) - Shahab, Amir Reza (My University, 2020)
This master thesis work was aimed for understanding the surface integrity and machinability of 316L stainless steel which was produced by two common methods of additive manufacturing called selective laser melting (SLM) and electron beam melting (EBM). Additive manufacturing is a new method of production for complex shape structures with less lead time and less waste of material. Samples of SLM were produced at RISE AB with SLM Solutions machine and samples of EBM were produced at Mid-Sweden university with ARCAM machine. The results of as-printed condition show that melt pools in EBM samples are larger that SLM ones. SLM samples have a cellular structure inside each melt pool. SLM samples have higher hardness than EBM however the surface roughness of SLM samples are lower than EBM. Lack of fusion features in EBM samples are in the size of less than one micron. Samples were machined (turning) from top and bottom in four steps. Depth of cut for each step is 0.25 mm. During turning, all 3 forces of cutting, feed and passive forces were recorded. All components of forces in step 1 are higher in SLM in comparison with EBM. Surface roughness after machining is around 0.9 micron for EBM and 0.8 micron for SLM. It is recommended to machine SLM samples for 1 passage with depth of cut of 0.25 mm. For EBM samples, it is recommended to machine the samples for 3 passages with depth of cut of 0.75 mm. Tensile residual stress exists after additive manufacturing due to rapid solidification of new layer in contact with an already solid layer. Machining will cause compressive stress which neutralizes the tensile stress to some extent. Maximum compressive stress will happen at depth of 10-30 micron under machined surface. In SLM, maximum compressive stress is higher in step1 in comparison with step 4. In EBM, maximum compressive stress is higher in step 4 in comparison with step 1.
Keywords: Additive manufacturing; SLM; EBM; Surface integrity; 316L stainless steel; Machining; Turning; Surface roughness; Residual stress; Microstructure